Cloacal Malformation with Associated Urethral Atresia - Al-Shamaileh, Tamador; Tiusaba, Laura; Jacobs, Shimon Eric; Russell, Teresa Lynn; Bokova, Elizaveta; Pohl, Hans G.; Varda, Briony K.; Ho, Christina; Feng, Christina; Badillo, Andrea; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2023)
Introduction Cloacal malformations comprise a heterogeneous group of anomalies that are considered the most complex anorectal malformations (ARMs) in females. Precise evaluation to identify the unique anatomy prior to reconstruction with collaboration between colorectal surgeons, urologists, and gynecologists is vital. Here, we present a rare anatomical variation in a patient with a cloacal malformation which affected operative and postoperative management.Case description A 6-year-old female with cloaca who underwent colostomy, vaginostomy, and vesicostomy as a newborn presented for reconstruction. Her VACTERL workup was negative except for an atretic right kidney. Her ARM index included the cloaca, a normal spine, and sacrum with a lateral sacral ratio of 0.7, predicting good potential for bowel continence. Cystoscopy through the vesicostomy showed a small bladder with normal ureteral orifices, and a closed bladder neck, with no identifiable urethra. A cloacagram showed an atretic common channel, a single small vagina, and a rectum below the pubococcygeal line. The patient underwent a posterior sagittal anorectovaginourethroplasty, vaginal patch using rectum, rectoplasty, and perineal body reconstruction. The urethra was not amenable to reconstruction, so the vesicostomy was preserved and a future Mitrofanoff was planned.Conclusion Urethral atresia is a rare and challenging finding in cloaca patients, and a vesicostomy is needed to drain urine in the newborn period. Preoperative examination under anesthesia, cystoscopy, vaginoscopy, and cloacagram are crucial to identify the precise anatomy and to plan accordingly.
Keywords: urethra atresia; cloaca; rectal patch